Systems Thinking in a Second Grade Curriculum: Students Engaged to Address a Statewide Drought - Curwen, Margaret Sauceda; Ardell, Amy; MacGillivray, Laurie; Lambert, Rachel (Frontiers in Education, 2018)
Faced with issues, such as drought and climate change, educators around the world acknowledge the need for developing students' ability to solve problems within and across contexts. A systems thinking pedagogy, which recognizes interdependence and interconnected relationships among concrete elements and abstract concepts (Meadows, 2008; Senge et al., 2012), has potential to transform the classroom into a space of observing, theorizing, discovering, and analyzing, thus linking academic learning to the real world. In a qualitative case study in one school located in a major metropolitan area in California, USA teachers and their 7- and 8-year-old students used systems thinking in an interdisciplinary project-based curriculum. Through reflection and investigations, students devised solutions and used innovative approaches to publicly engage peers and family members in taking action to address an environmental crisis.